The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1172/jci108340
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of guanidinosuccinic acid by perfused rat liver.

Abstract: A B S T R A CT The metabolic pathway for the synthesis of guanidinosuccinic acid was studied in the rat. Labeled guanidinosuccinic acid was isolated from the urine of animals given L-[guanidino-14C]arginine intraperitoneally but did not appear in the urine after administration of D,L-[guanidino-14C]canavanine. Radioactive arginine and nonradioactive aspartic acid and arginine were infused in the isolated, perfused rat liver. After 20 min, small amounts of both labeled and unlabeled guanidinosuccinic acid and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…HPLC has been used for the analysis of arginine and its metabolites (15,19,20). The HPLC examination of the acid-soluble substances demonstrated that the distribution of radioactive acid-soluble substances depend on the organs and the intervals after injection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC has been used for the analysis of arginine and its metabolites (15,19,20). The HPLC examination of the acid-soluble substances demonstrated that the distribution of radioactive acid-soluble substances depend on the organs and the intervals after injection.…”
Section: Resultsmentioning
confidence: 99%
“…The results by HPLC showed that urea and guanidinosuccinic acid were the principal metabolites in the organs examined. Guanidinosuccinic acid, has been detected in the liver of uremia rats (21) and in the liver and kidney of normal rats (19,20), is formed from transamidination of arginine to aspartic acid (20). On the other hand, the interorgan flow of arginine is an important issue in relation to the urea cycle and critical nature of the extrahepatic economy (4).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic pathways of guanidinosuccinate remain incompletely understood [6,[29][30][31]. The relation between guanidino compound metabolism and inflammation has not been investigated thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…Guanidinosuccinate and guanidinopropionate can inhibit neutrophil superoxide production [30,32] and a mixture of guanidino compounds was found to suppress the natural killer cell response to interleukin-2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…In cytoplasm, aspartic acid is used as cosubstrate of arginino-succinate synthetase, and in the pyrimidine synthesis. It is also used in the biosynthesis of guanidinosuccinic acid (16). The reason why^the aspartic acid values in erythrocytes of patients with hyperargininemia fall to the plasma values is not yet clear.…”
Section: Discussionmentioning
confidence: 99%